Nanoparticles-reinforced poly-l-lactic acid composite materials as bioresorbable scaffold candidates for coronary stents: Insights from mechanical and finite element analysis. (January 2022) - Toong, Daniel Wee Yee; Ng, Jaryl Chen Koon; Cui, Fangsen; Leo, Hwa Liang; Zhong, Liang; Lian, Shaoliang Shawn; Venkatraman, Subbu; Tan, Lay Poh; Huang, Ying Ying; Ang, Hui Ying
Abstract: Current generation of bioresorbable coronary scaffolds (BRS) posed thrombogenicity and deployment issues owing to its thick struts and overall profile. To this end, we hypothesize that the use of nanocomposite materials is able to provide improved material properties and sufficient radial strength for the intended application even at reduced strut thickness. The nanocomposite formulations of tantalum dioxide (Ta2 O5 ), L-lactide functionalized (LA)-Ta2 O5, hydroxyapatite (HA) and LA-HA with poly-l-lactic acid (PLLA) were evaluated in this study. Results showed that tensile modulus and strength were enhanced with non-functionalized nanofillers up until 15 wt% loading, whereas ductility was compromised. On the other hand, functionalized nanofillers/PLLA exhibited improved nanofiller dispersion which resulted higher tensile modulus, strength, and ductility. Selected nanocomposite formulations were evaluated using finite element analysis (FEA) of a stent with varying strut thickness (80, 100 and 150 μm). FEA data has shown that nanocomposite BRS with thinner struts (80–100 μm) made with 15 wt% LA-Ta2 O5 /PLLA and 10 wt% LA-HA/PLLA have increased radial strength, stiffness and reduced recoil compared to PLLA BRS at 150 μm. The reduced strut thickness can potentially mitigate issues such as scaffold thrombosis and promote re-endothelialisation of the vessel. Graphical abstract: Image 1